Recognition of Anterior Peritoneal Reflections and Their Relationship With Rectal Tumors Using Rectal Magnetic Resonance Imaging. Issue 9 (March 2016) - Yiqun, Sun; Tong, Tong; Fangqi, Liu; Sanjun, Cai; Chao, Xin; Yajia, Gu; Ye, Xu
Abstract : Abstract: Our goal was to explore the factors influencing the visualization of anterior peritoneal reflections (APRs) using rectal MRI. We evaluated the usefulness of rectal MRI in measuring the distance from the anal verge to the APR and determining the relationship between the APR and the rectal tumor. Clinical and imaging data from 319 patients who underwent surgery after MRI examination between October 2010 and December 2013 were retrospectively analyzed. The distance from the anal verge to the APR and the relationship between the APR and the location of the rectal tumor was evaluated. analysis of variance, logistic regression, independent samples t tests, and Kappa tests were used for statistical analysis. The APR was visible in 283 of 319 cases using rectal MRI. The APR was more readily observed in patients who were older than 58 years ( P = 0.046), in patients whose subcutaneous fat thicknesses were >22.2 mm ( P = 0.004), in patients with nondistended bladders ( P = 0.001), and in those with an anteversion of the uterus ( P = 0.001). There was a significant difference between the distance from the anal verge to the APR between females (10.4 ± 1.1 cm) and males (10.0 ± 1.2 cm; P = 0.014). The accuracy in predicting tumor location with respect to the APR was 70%, 50%, 98.2%, respectively for patients with tumors located above, at, and below the APR (compared with the location determined during surgery). Most of the APRs were visible using rectal MRI, whereas certain internal factors influence visualization. Rectal MRI could be a useful tool for evaluating the distance from the anal verge to the APR and relationship between rectal tumors and the APR.